Subjecthood in Spanish meteorological verbs - Diego Gabriel Krivochen (Isogloss)
In this paper we provide an analysis of meteorological verbs that allows us to account for their distribution in coordinated structures with a non-overt subject in the second conjunct, of the kind it snowed and covered the tracks, focusing on Spanish data. We argue that verbs like rain and snow, in their pure meteorological uses share with unergatives such as laugh the property of being denominal, and that in Spanish they appear in defective structural configurations that do not license a specifier for vP/VP or TP. We propose that (i) the nominal in the lexical derivation of meteorological predicates remains accessible for a limited range of syntactic processes and (ii) Spanish meteorological sentences are subject-less. Under these assumptions, we provide a novel analysis of apparent ‘subject’ omission in coordinated structures with meteorological predicates.